1988
DOI: 10.1139/b88-025
|View full text |Cite
|
Sign up to set email alerts
|

Dormancy and survival in buried seeds of proso millet (Panicum miliaceum)

Abstract: Survival, dormancy, and germination of buried seeds of 30 populations of proso millet (Panicum miliaceum L.) were investigated. The effects of duration and depth of burial and type of soil were considered. The 30 populations belong to three agronomic groups: crop, croplike weed, and black-seeded weed. Black seeds exhibited much greater overwinter survival and dormancy than did seeds of the other two groups. Crop seeds had almost no survival through the winter. Only one croplike weed population exhibited apprec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
1
1

Year Published

1989
1989
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 0 publications
2
27
1
1
Order By: Relevance
“…In overwinter survival studies on seeds of this biotype, Colosi et al (1988) also found differences between populations. Two populations separated only by a road were more different from each other in survival, germination, and dormancy than each of them was from the average of nine populations spread across southern Ontario.…”
Section: Comparisorl Between Populationsmentioning
confidence: 77%
“…In overwinter survival studies on seeds of this biotype, Colosi et al (1988) also found differences between populations. Two populations separated only by a road were more different from each other in survival, germination, and dormancy than each of them was from the average of nine populations spread across southern Ontario.…”
Section: Comparisorl Between Populationsmentioning
confidence: 77%
“…It has long been suggested that soil characteristics like texture and aggregate structure can affect seed bank dynamics in agricultural fi elds (Brenchley and Warington, 1930;Paatela and Erviö, 1971;Pareja and Staniforth, 1985;Colosi et al, 1988). The most important difference between the three soil types compared in this study was related to texture and stoniness.…”
Section: Seed Bank Heterogeneitymentioning
confidence: 69%
“…Russell-Smith and Lucas, 2009); for example, Kellman (1974) found a negative effect of acidic pH on species richness. Perhaps the most important soil physical trait affecting seed banks is soil texture, as different textures can aid or restrict the entrance of seeds into the soil, and later they can trigger differential germination responses because of differences in water retention, the probability of seeds to become scarifi ed under a given soil particle size distribution, and the differences in soil porosity and the consequent differential gas exchange and light penetration (Paatela and Erviö, 1971;Vincent and Cavers, 1978;Pareja and Staniforth, 1985;Colosi et al, 1988;Wild, 1993;Baskin and Baskin, 1998).…”
mentioning
confidence: 99%
“…The longevity of seeds in the seed bank varies from very brief, less than one year and often only a few weeks, to strongly persistent over several to many years (Bough et al 1986;Colosi et al 1988;Cavers et al 1992; J.J. O'Toole, personal communication). At one extreme, in Ontario, seeds of the White biotype of P. miliaceum almost never survive in the soil for more than a few weeks and more than 99% cannot overwinter successfully in the field .…”
Section: (C) Seed Banks Seed Viability and Germination (I) Predominamentioning
confidence: 99%